Fine-tuning d-p hybridization in Ni-B x cocatalyst for enhanced photocatalytic H2 production - Haoyu Long; Xidong Zhang; Zhenyi Zhang; Jianjun Zhang; Jiaguo Yu; Huogen Yu (Nature Communications)
Abstract The H2-evolution kinetics play a pivotal role in governing the photocatalytic hydrogen-evolution process. However, achieving precise regulation of the H-adsorption and H-desorption equilibrium (Hads/Hdes) still remains a great challenge. Herein, we propose a fine-tuning d-p hybridization strategy to precisely optimize the Hads/Hdes kinetics in a Ni-B x modified CdS photocatalyst (Ni-B x /CdS). X-ray absorption fine-structure spectroscopy and theoretical calculations reveal that increasing B-atom amount in the Ni-B x cocatalyst gradually strengthens the d-p orbital interaction between Ni3d and B2p , resulting in a consecutive d-band broadening and controllable d-band center on Ni active sites. The above consecutive d-band optimization allows for precise modulation of the Hads/Hdes dynamics in the Ni-B x /CdS, ultimately demonstrating a remarkable H2-evolution activity of 13.4 mmol g-1 h-1 (AQE = 56.1 %). The femtosecond transient absorption spectroscopy further confirms the rapid electron-transfer dynamics in the Ni-B x /CdS photocatalyst. This work provides insights into the optimal design of prospective H2-evolution catalysts.